As dimensões estratégia e sócio-comunicacional da rede de terceirização: impactos e perspectivas na visão gerencial, sindical e dos trabalhadores terceirizados na Petrobrás - Bicudo, Valéria Rosa (2002)
The objective of this work was to study the implications/impacts (social, management and political) of outsourcing making new type of capitalistic competition feasible by means of inter-company networks in segment of the petroleum industry. Thus, an empiric research having the industrial maintenance sector of petroleum refinery in Rio de Janeiro as investigatory material, was developed during the period between 1999 to 2001. The different lenses (optical) of the social subjects involved were considered in this investigation. which are: management, unions and the outsourced workers themselves. The study of the results demonstrated that outsourcing in the segment of the industry researched has implied simultaneous movements of destruction/re-construction of traditional productive relationships, combining modernization and organization of network production with Taylorist/Fordist practices. New and old forms of (de) socialization and uncertainty can be see through the discrepant salary and work conditions and in the creation of two categories of workers: petroleum industry workers and the segment of sub-contracted workers. Based on this study, the ambiguity and fragility of this outsourcing 'network' becomes very clear, because the concentration of power and resources at specific points and the prevalent instrumental and economist aspect to the detriment of dialogue results in withdrawal from the very principie of inter-dependency that is inherent within the idea of network. The manner in which outsourcing is being implemented in this industry is becoming closer to predatory standard than that of flexible and inter-dependent standard with characteristics inherent to the management concept of the network. Besides this, the mechanisms employed in social and economic admission/exclusion among outsourced workers, indicates different citizenships within the ambit of the company, demonstrating the co-existence of new and old forms of exploitation under the network paradigm